Aggregation-Induced Polarization (AIP): Optical Rotation Amplification and Adjustment of Chiral Aggregates of Folding Oligomers and Polymers - Tang, Yao; Zhang, Sai; Xu, Ting; Yuan, Qingkai; Wang, Jia-Yin; Jin, Shengzhou; Wang, Yu; Pan, Junyi; Griffin, Isaac; Chen, Daixiang; Li, Guigen (Frontiers in Chemistry, 2022)
The phenomenon of aggregation-induced polarization (AIP) was observed showing optical rotation amplification and adjustment. The relationship between optical rotations of chiral aggregates of multi-layered chiral folding oligomers and polymers with water% in THF (fw) has been established accordingly. New multi-layered chiral oligomers were synthesized under the asymmetric catalytic systems established by our lab recently. These products were well characterized UV-vis, NMR and MALDI-TOF spectra. Absolute stereochemistry (enantio-and diastereochemistry) was assigned by comparison with similar asymmetric induction by the same catalyst in our previous reactions. The present AIP work can serve as a new tool to determine chiral aggregates, especially for those that cannot display emission. AIP would also complement AIE-based CPL since AIP serves as a new tool providing enhanced right- or left-hand polarized lights with individual wavelengths. It will find many applications in chemical and materials sciences in the future.